Анализ технологии создания инфрастуктуры для разработки и развертывания программных приложений - Ходякова, Г.В.; Поздеев, В.А.; Ходякова, Н.В. (Управляющие системы и машины, 2019)
Рассмотрена тенденция развития инфраструктуры для создания и развертывания программных приложений и технологии использования виртуальных машин, контейнеров, платформ для развертывания приложений, оркестровщиков контейнеров, а также классификация перечисленных технологий. Приведен пример установки и использования Docker и два варианта создания Docker-контейнеров. Мета статті. Аналіз технологій організації інфраструктури для створення і розгортання програмних додатків та їх класифікація. Методи. У статті проводиться огляд різних технологій для вирішення завдань створення незалежності програми від середовища виконання з тим, щоб повністю абстрагувати функції адміністрування. У цьому напрямку розвивається інфраструктура створення і використання програмних продуктів. Результати. Описано засоби і технології, що забезпечують сумісність середовища розробки та запуску додатків, а також, в якому напрямку останнім часом розвивається інфраструктура створення та розгортання програмних додатків. Це контейнерні технології, платформи для розгортання додатків, оркестровщик контейнерів. Розглянуті технології ми класифікували за рівнем абстрагування від інфраструктури, доступної розробникам. Наводиться також приклад практичної реалізації на комп'ютері процесу установки Docker і два варіанта створення Docker-контейнерів. Purpose. This article aims at considering evolution dynamics and classification of modern means and technologies that ensure compatibility of development environment and applications that are developed and executed in this environment. Methods. In this article various technologies for solving problems of creating environment-independent software with the purpose of abstracting management tasks are analyzed, widely used virtual machines and their drawbacks are briefly overviewed. A summary and classification of other means accompanying software development and deployment are given. Results. The evolution trends of modern means and technologies that ensure the compatibility between development environment and applications that are developed and executed in this en-vironment such as virtual machines, container technologies and their classification are considered. The trends of software creation and operation infrastructure are described, abstraction levels of in-frastructure available to developers are marked out. A practical example of Docker container management system installation and the usage is provided, as well as of a load balancer operation mechanism.